2016
DOI: 10.1007/s00107-016-1102-6
|View full text |Cite
|
Sign up to set email alerts
|

Strength grading on the basis of high resolution laser scanning and dynamic excitation: a full scale investigation of performance

Abstract: Effective utilization of structural timber requires grading and indicating properties (IPs) that are able to predict strength with high accuracy and machines that are able to measure the underlying board properties at a speed that corresponds to the production speed of sawmills. The aim of this research is to assess the performance of a new machine strength grading method/procedure which was recently approved for the European market and to compare the performance of it with the performance of other available t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 6 publications
5
56
0
Order By: Relevance
“…Prior to the test, the modulus of elasticity (E) and the bending strength of the beam were assessed by means of high-resolution laser scanning and dynamic excitation. 26 Information of the tested beam is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the test, the modulus of elasticity (E) and the bending strength of the beam were assessed by means of high-resolution laser scanning and dynamic excitation. 26 Information of the tested beam is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Employing a nearest-neighbour interpolation, the stiffness values are homogenised over each cross section, resulting in a stiffness profile for each board. In Olsson and Oscarsson (2017), it has been shown that the weakest value in such a stiffness profile correlates well to the strength of a single board.…”
Section: Stiffness Profilesmentioning
confidence: 99%
“…In addition, an approach of directly employing the stiffness profiles E(x) was pursued. This approach is inspired by the promising procedure presented in Olsson et al (2013), Oscarsson et al (2014), and Olsson and Oscarsson (2017). Therein, the minimum value of the stiffness profile E(x) of a board is assumed to present the weakest defect.…”
Section: Simplified Models For Prediction Of Glt Stiffness and Strengthmentioning
confidence: 99%
“…For determining the mechanical properties of individual timber boards, data acquired through laser scanning is used [4]. Based on the obtained data, the 3D knot geometry is reconstructed automatically [5].…”
Section: Materials Model For Timber Boardsmentioning
confidence: 99%